Embedding patient and public involvement into a doctoral study: developing a point-of-care HIV testing intervention for dental settings - Doughty, J.; Preston, J.; Paisi, M.; Hudson, A.; Burns, F.; Porter, S. R.; Watt, R. G. (Frontiers in Oral Health, 2024)
Introduction Patient and Public Involvement (PPI) can have a positive impact on research. PPI can make research more meaningful and appropriate as well as preventing research waste. For decades, patient advocates with HIV have played a key part in public health and research. This article presents the PPI activity undertaken during a doctoral study. The aim of this article is to demonstrate how PPI was embedded into a doctoral study that explored the feasibility of HIV testing in dental settings. Methods Patients and the public were invited to be involved with the feasibility study through various organisations and charities. A comprehensive PPI activity strategy was devised, and appropriate funding was obtained. Patients and the public were predominantly consulted or collaboratively involved with several aspects of the study. Findings Patients and the public positively contributed to the intervention development and the resources supporting its implementation. As a result, the study resources (i.e., questionnaire and information leaflets) were easier to read, and the intervention was more appropriate to the needs of patients. Furthermore, the training and focus groups conducted with dental patients and people with HIV benefitted from input of people with lived experience. Conclusions PPI can be embedded within doctoral studies provided there is sufficient funding, flexibility, and supervisory support. However, PPI activity may be impacted by limited resource and a priori research protocol and funding agreements.